Scalable electrospinning using a desktop, high throughput, self-contained system - Tessa S. Gilmore; Pelagia-Irene Gouma (Scientific Reports)
Abstract Electrospinning is a specialized processing technique for the formation of submicron diameter fibers of polymeric and ceramic materials using an electrostatic field. The process has multiple advantages over other nano- and micro- fiber synthesis methods; however, generally suffers from very low fabrication speeds, making it undesirable for scalability. This work assesses the performance of a needle-less, self-contained, high throughput electrospinning system. It further compares the fiber fabrication rates obtained versus two single needle setups with different collectors: (i) a conventional single needle and flat plate geometry, and (ii) a single needle with a rotating collector geometry. Polyvinylpyrrolidone (PVP) in ethanol was used as the model material. The fabrication rate of the high throughput system “HTES” was measured at about 2.6 g/h and was about 15 times that collected of the flat plate. Comparing it to other systems reported in the literature also proved it to be a viable option for high throughput, lab scale electrospinning.